Influence of treatment in weak magnetic fields on photoluminescence of GaN:Si - Red’ko, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The long-term transformations of photoluminescence of GaN:Si treated with pulsed weak magnetic fields have been studied. The defect structure transformations have been inferred from the radiative recombination spectra within the range 350…650 nm at 300 K. A possible mechanism of observed modifications related with the magnetic field induced destruction of metastable complexes has been discussed.